2018
DOI: 10.1007/8904_2018_98
|View full text |Cite
|
Sign up to set email alerts
|

Alkaptonuria Severity Score Index Revisited: Analysing the AKUSSI and Its Subcomponent Features

Abstract: PCA and redundancy analysis supported the AKUSSI as a robust AKU disease severity measure, although some AKUSSI features could be removed for simplicity. For small patient populations and rare diseases, PCA and redundancy analysis together can aid validation of disease severity metrics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…As AKU research has gathered traction and more patients have become involved in research, the AKUSSI has clearly demonstrated the effect of nitisinone on the various parameters of the index. It shows how effective the therapy is, adding further validation to its use in AKU, it reduces HGA but also demonstrates numerous secondary important features of monitoring patients and their tissues which become symptomatic during the course of the disease [77,78]. The efficacy of nitisinone is clearer seen in longitudinal studies spanning 3 years examining multiple patients with AKU, not only reducing HGA, but also arresting ocular and auricular ochronosis [59].…”
Section: Effectiveness Of Nitisinone In Akumentioning
confidence: 87%
“…As AKU research has gathered traction and more patients have become involved in research, the AKUSSI has clearly demonstrated the effect of nitisinone on the various parameters of the index. It shows how effective the therapy is, adding further validation to its use in AKU, it reduces HGA but also demonstrates numerous secondary important features of monitoring patients and their tissues which become symptomatic during the course of the disease [77,78]. The efficacy of nitisinone is clearer seen in longitudinal studies spanning 3 years examining multiple patients with AKU, not only reducing HGA, but also arresting ocular and auricular ochronosis [59].…”
Section: Effectiveness Of Nitisinone In Akumentioning
confidence: 87%
“…Further, our analyses were performed using a larger and more geographically dispersed sample than previous assessments of the cAKUSSI, and included both nitisinone‐treated and untreated patients, allowing assessment of how well alternative AKUSSI versions captured treatment response. 9 …”
Section: Discussionmentioning
confidence: 99%
“…Authors' expert opinion was also used to validate measurements suggested for removal by the statistical methods described below. (2) Principal component analysis (PCA) was used to analyse the contribution of each measurement to the variation in cAKUSSI score data, and therefore its ability to distinguish between patients of different disease severities, as per Langford et al 9 PCA was performed separately at each timepoint and results were compared to determine consistency over time. Relative weights from the first four principal components were used to identify which cAKUSSI components contributed most to the variation in the data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed evaluation and comparison of clinical and genomic data of sibling patient pairs can be a key to understanding its variability. A disease severity index for AKU 32 (AKUSSI) and other clinical and biochemical features can serve for careful monitoring of disease status, and the influence of non-AKU genes can be evaluated, including those responsible for aging and osteoarthritis susceptibility.…”
Section: Genotype-phenotype Correlationsmentioning
confidence: 99%